Selection history-driven signal suppression. Issue 2 (7th February 2020) - Anderson, Brian A.; Kim, Andy Jeesu
ABSTRACT: The control of attention is influenced by current goals, physical salience, and selection history. Under certain conditions, physically salient stimuli can be strategically suppressed below baseline levels, facilitating visual search for a target. It is unclear whether such signal suppression is a broad mechanism of selective information processing that extends to other sources of attentional priority evoked by task-irrelevant stimuli, or whether it is particular to physically salient perceptual signals. Using eye movements, in the present study we highlight a case where a former-target-colour distractor facilitates search for a target on a large percentage of trials. Our findings provide evidence that the principle of signal suppression extends to other sources of attentional priority beyond physical salience, and that selection history can be leveraged to strategically guide attention away from a stimulus.